Math

posted by .

Find the perimeter of the cord r=a(1+cos theta)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    put these polar equations into cartesians form: 1) theta=135 degrees 2)rcostheta=-1 for #1 is it like: (-1,1)?
  2. Optimization

    min 2x+y subject to: x+y+z=1 and y^2+z^2=4 Any help would greatly be apprecaited. y^2+z^2=4 ---> put y = 2 cos(theta) and z = 2 sin(theta) x+y+z=1 ----> x = 1-2(cos(theta) + sin(theta)) 2x + y = 2 - 2 cos(theta) - 4 sin(theta) …
  3. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  4. Physics

    An object is shot at 20m/s at an angle theta. The object lands 24m away. What is the angle?
  5. math (trig)

    if cos 2 theta = -(1/3) and theta is in Quadrant 2, find sin theta, cos theta, tan theta, and draw triangle theta
  6. math

    Another: theta is a second quadrant angle in standard position and tan theta = - (sqrt5)/(2) . Find the exact value of cos theta. I assume I use the equation 1 / cos(theta)^2 = 1 + tan (theta)^2 However how does this work out algebraically?
  7. math

    knowing that 2(theta) can be written as theta + theta, find the expression for sin2(theta) and cos2(theta). Is it 2sin(theta)cos(theta)?
  8. Math - Trigonometry

    Let f(x) be a polynomial such that f(cos theta) = cos(4 theta) for all \theta. Find f(x). (This is essentially the same as finding cos(4 theta) in terms of cos theta; we structure the problem this way so that you can answer as a polynomial. …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions